Literature Review: Peningkatan Hasil Belajar Kognitif Dan Motivasi Siswa Pada Materi Biologi Melalui Model Pembelajaran Guided Inquiri - Desi Gita Lestari; Hani Irawati (BIOMA: Jurnal Biologi dan Pembelajarannya, 2020)
The success of the learning process is inseparable from the ability of the teacher to apply creative and innovative learning models, in order to provide a stimulus for students to be more active in the learning process. The teacher-centered teaching and learning process has an impact on students who do not have learning motivation and an impact on low student learning outcomes. This study aims to determine the increase in cognitive learning outcomes and student motivation with the Guided Inquiry learning model on biology material with literature review analysis. This research is a literature review study with the type of narrative review. There are 30 scientific articles used in this research from 1 international journal, 25 accredited national journals, and 4 proceeding articles. The data presentation technique uses a table listing scientific publication articles which will be analyzed into research data. The data analysis technique was carried out qualitatively descriptive by analyzing and identifying scientific articles to produce a more informative summary. The results of literature review research indicate that the Guided Inquiri model can improve student cognitive learning outcomes and motivation. The Guided Inquiri learning model has advantages that make students able to develop intellectual abilities, communicate, and solve problems. The Guided Inquiry learning model combined with media and learning strategies can provide a significant increase in student activity.